A streamlined approach for assessing the Allostatic Load Index in industrial employees - Mauss, Daniel; Jarczok, Marc N.; Fischer, Joachim E. (Stress, 2015)
Work stress is common and can lead to various bodily dysfunctions. The Allostatic Load Index (ALI) is a tool to measure the wear and tear of the body caused by chronic stress. This cross-sectional study aimed to explore the association of work-related stress and ALI in German industrial employees. A short form ALI should be developed for practical use of company physicians. In this exploration of an industrial cohort (n = 3797; 79.3% male), work stress was measured by the effort-reward imbalance (ERI) questionnaire in 2009-2011. ALI was calculated using 15 variables including anthropometric data, heart rate variability, as well as blood and urine samples based on predefined subclinical cut-off values. Differences in ALI related to low (≤1) and high (>1) ERI categories were tested. Logistic regression models estimated odds ratios (ORs) and corresponding 95% confidence intervals (CIs) for the association between ALI and work stress controlling for multiple confounders. Employees exposed to high work stress showed higher ALI scores (p < 0.001) compared to those with low stress levels. In multivariable models, ALI was associated with work stress (OR 1.19 [95% CI: 1.00, 1.42]; p < 0.05) following adjustment for a range of potential confounders. By reducing ALI parameters to five variables this association increased modestly and remained statistically significant (OR 1.27 [95% CI: 1.05, 1.54]; p < 0.05). The results indicate that work stress is associated with ALI in German industrial employees. A short form index seems to be a promising approach for occupational health practitioners. The results should be validated in further longitudinal explorations defining a standard set of variables including gender-related thresholds.